Vitamin-Mineral Supplement Use Patterns in Elderly Koreans: Data from the 2007–2008 Korean National Health and Nutrition Examination Survey - Park, So Young (Korean J Fam Med, 2016)
BACKGROUND: Vitamin-mineral supplements are the most popular dietary supplements in Korea. However, few studies have assessed the relationship between vitamin-mineral supplementation and associated factors among the Korean elderly. The purpose of this study was to assess the use of vitamin-mineral supplements among elderly in Korea as well as its association with sociodemographic factors, health-related behaviors, medical conditions, and nutrient intake. METHODS: This study was based on data from the Korean National Health and Nutrition Examination Survey, conducted by the Korean Ministry of Health and Welfare from 2008 to 2009. Data from 3,294 elderly men and women (65 years of age and older) were analyzed. Multivariable-weighted logistic regression model analysis was used to evaluate the association between vitamin-mineral supplement use and sociodemographic factors, health-related habits, and medical conditions. RESULTS: Vitamin-mineral supplementation was reported by 16.3% of the participants. The most common reason for using dietary supplements was recommendations from friends and acquaintances. Highly educated person, female participants had a greater likelihood of taking vitamin-mineral supplements. In addition, analysis of nutrient intake from food sources alone revealed a lower proportion of vitamin-mineral supplement users with nutrient intakes below the estimated average requirements for vitamin A, vitamin C, thiamine, riboflavin, niacin, calcium, iron, and phosphorus, compared to nonusers. However, vitamin-mineral supplementation was not associated with health-related behaviors or medical conditions. CONCLUSION: Highly educated person, elderly Korean women had a greater likelihood of using vitamin-mineral supplements. In addition, nutrient intakes from food sources alone were significantly higher among vitamin-mineral supplement users. Finally, vitamin-mineral supplementation may be an indicator of healthier diet in elderly Koreans.